CuS nanosheet-induced local hot spots on g-C3N4 boost photocatalytic hydrogen evolution. (22nd February 2023) - Xue, Fei; Wu, Haochen; Liu, Yuting; Min, Moya; Hatami, Mohammad; Li, Naixu; Liu, Maochang
Abstract: An ideal model composite made of CuS nanosheet (photothermal material) and g-C3 N4 was constructed through in-situ assembly procedure, along with integration of dual photochemical effect and photothermal effect. Consequently, optimized CN/CuS composite approaches remarkable photocatalytic performance improved by 44.5 times with regarding to that of pristine CN. This superiority can be assignable to inherent characteristic of CuS as photochemical component, with improved charge separation and enriched surface active-sites. Additionally, the critical contribution of photothermal effect in boosting water photosplitting was also experimentally validated. CuS nanosheet as hot spots enables rapid temperature increment around photocatalysts under visible/near-infrared (NIR) light irradiation. The heat converted from solar is conducive to increase carrier density, accelerate carrier mobility, alleviate onset potential and facilitate surface redox kinetics, so as to promote photocatalytic activity. It is believed that synergetic incorporation of photothermal and photochemical conversion could be expanded to other photocatalytic systems towards effective solar energy conversion. Highlights: CuS hot spot was integrated with g-C3 N4 in 2D-2D contact by in-situ assembly method. CuS induced photothermal effect plays a critical role in boosting photocatalytic rate. Photochemical/photothermal synergistic catalysis boosts H2 evolution by 44.5 times.